Studies on Paracoagulation. Role of Antithrombin VI - Kopeć, Maria; Kowalski, Edward; Stachurska, Jolanta (Thrombosis and Haemostasis, 1961)
1. Conditions in which paracoagulation occurs were studied.2. It could be shown, that instead of protamine sulphate and toluidine blue, lysozyme, cooling to 4° C and acidification to pH 5,3—6,1 induce paracoagulation.3. Paracoagulation could be obtained in the presence of antithrombin VI in purified systems consisting either of fibrinogen or fibrin monomer.4. It could be stated, that antithrombin VI inhibits the polymerization of fibrin monomer and probably interferes with the protease activity of thrombin.5. Paracoagulating factors overcome the inhibitory action of antithrombin VI.6. The significance of the above findings is discussed.